Integrated Approach to Flood Risk Management: A Comprehensive Thematic Review in the Malaysia Context - Saad, Mohammad Syamsyul Hairi; Ali, Mohamad Idris; Razi, Putri Zulaiha; Ramli, Noram Irwan; Bawono, Adi Setiabudi (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
This research addresses a need in the literature on flood risk management in Malaysia, particularly as it relates to development projects. Understanding and improving risk management strategies is crucial as Malaysian floods increase. A thematic literature review was used to search relevant 2018–2023 literature. It exhaustively searched scholarly databases, and government, and international organization reports. Multi-thematic analysis was used to understand the flood risk management narrative. The study shows that Malaysian flood risk management strategies need a more holistic and integrated approach. The development of an integrated framework is a significant step forward because it allows for the better coordination of developmental project initiatives with strategies meant to mitigate and manage flood risks. Effective collaboration between the federal government, Malaysian local authorities, urban planners, developers, and construction firms is crucial. Effective flood management requires accurate risk assessment by consultants, developers, and local authorities to integrate current and future development projects in flood-prone areas. Project development requires strategy, overview, and flood risk assessment in planning permission can produce creative and secure results.